PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN POMPA AIR MEREK SHIMIZU PADA PT PANCAMAS PIPASAKTI - Israndi, Hafid; Fahlevi Almassawa, Syafieq (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the effect of brand image and Price on Purchasing Decisions on Shimizu Water Pumps at PT Pancamas Pipasakti. The ntitative method. The sampling technique uses the Slovin formula, so tha obtained research method used is descriptive quantitative method. descriptive qua a sample of 81 respondents.While the primary data collection technique is through a questionnaire which is processed. The data analysis method uses the validity test, reliability test, classical assumption test, regression analysis, coefficient of data analysis. validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient, and hypothesis testing. correlation coefficient, coefficient of determination, and hypothesis testing. The results of this study are Brand Image has a positive and significant effect on purchasing decisions with a coefficient of determination determination coefficient of 49.8%, and hypothesis testing obtained tcount> ttable (8.853> 1.991). or a significance of 0.000 <0.05. Price has a positive and significant effect on purchasing decisions with a coefficient of determination of 50.6% and hypothesis testing obtained tcount> ttable (8.993> 1.991) or a significance of 0.000 <0.05. Brand image and price simultaneously have a positive and significant effect on purchasing decisions with the regression equation Y = 13.577 + 0.540X1 + 0.586X2. The coefficient of determination is 60.4%, while the remaining 39.6% is influenced by other factors. Hypothesis testing obtained Fcount> Ftabel or (59.433> 2.721).